11 Do firearm regulations work? evidence from the australian national firearms agreement. (19th September 2017) - Andreyeva, Elena; Ukert, Benjamin
Abstract : In 1996, following a mass shooting that killed 35 people near Port Arthur, Tasmania, the Australian government responded by promptly securing agreement from all states to implement stricter firearm regulations. The set of newly proposed firearm regulations became the National Firearms Agreement (NFA). Its goal was to achieve uniformly stricter regulations across states to minimise the likelihood of future mass shootings. The most important legislative achievements of the NFA included a federal ban on the sale, transfer, importation and ownership of certain types of long firearms, heavier restrictions on civilian ownership of all types of firearms, and a federal buyback program. This paper estimates the causal effect of the NFA on firearm and non-firearm mortality. Our main specification estimates difference-in-differences models relying on cross-sectional variation in the pre-NFA average state firearm mortality rates from 1994 to 1996. Our preferred specification suggests that the NFA decreased the total firearm mortality rate by 2.21 deaths per 1 00 000 people in a state with the average 1994–1996 pre-treatment total firearm mortality rate. This change translates into a 61% decrease in the total firearm mortality rate from pre-NFA levels. The decrease in the total firearm mortality rate emerges from 0.75 deaths per 1 00 000 people reduction in the firearm homicide rate, and 1.30 deaths per 1 00 000 people reduction in the firearm suicide rate. Overall, we demonstrate that the comprehensive Australian firearm regulations indeed contributed to a decline in firearm mortality.